Late Transition Metal Olefin Polymerization Catalysts Derived from 8-Arylnaphthylamines - Zonglin Qiu; Wenyan Wang; Handou Zheng; Dengfei Wang; Xinglong Zhao; Guangshui Tu; Jiahao Yang; Haiyang Gao (Inorganics)
Late transition metal catalysts represent a significant class of olefin polymerization catalysts that have played an essential role in advancing the polyolefin industry owing to their highly tunable ligands and low oxophilicity. A key feature for the design of late transition metal catalysts lies in the steric bulk of the o-aryl substituents. Bulky 8-arylnaphthylamines have emerged as a promising aniline candidate for conducting high-performance catalysts by introducing axially steric hindrance around the metal center. This review focuses on late transition metal (Ni, Pd, Fe) catalysts derived from 8-arylnaphthylamines, surveying their synthesis, structural features, and catalytic applications in olefin (co)polymerizations. Additionally, the relationship between catalyst structure and catalytic performance is discussed, highlighting how these unique ligand systems influence polymerization activity, molecular weight, and polymer branching.